2011
DOI: 10.1007/s13595-011-0015-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-phase stratification treatments on seed germination in ash

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Blake, Taylor & Finch‐Savage () and Villiers () describe physical and hormonal changes inside stratified seeds associated with breaking embryo dormancy. In moist seeds at room temperatures (18–20 °C), embryos complete their development within 14 weeks (Doody & O'Reilly ). The rate of growth is not affected by previous low temperature treatment, but is significantly accelerated by removal of the indehiscent pericarp that has been suggested to be impermeable to oxygen (Villiers & Wareing ) and will delay embryo growth during the first winter.…”
Section: Floral and Seed Charactersmentioning
confidence: 99%
See 1 more Smart Citation
“…Blake, Taylor & Finch‐Savage () and Villiers () describe physical and hormonal changes inside stratified seeds associated with breaking embryo dormancy. In moist seeds at room temperatures (18–20 °C), embryos complete their development within 14 weeks (Doody & O'Reilly ). The rate of growth is not affected by previous low temperature treatment, but is significantly accelerated by removal of the indehiscent pericarp that has been suggested to be impermeable to oxygen (Villiers & Wareing ) and will delay embryo growth during the first winter.…”
Section: Floral and Seed Charactersmentioning
confidence: 99%
“…Without chilling, no germination takes place; Villiers () reports keeping unchilled, fully imbibed for over 6 years without any germination. The general prescription for breaking dormancy is moist warmth (15–20 °C) for 12–16 weeks followed by moist cold (2–5 °C) for another 12–16 weeks (Tylkowski ) although Doody & O'Reilly () found that germination increased as the duration of warm conditions increased up to 18–30 weeks, further releasing the embryo chemically and physically. Seeds from areas with cold winters need a longer period of warm and cold stratification to break dormancy (Farcas ).…”
Section: Floral and Seed Charactersmentioning
confidence: 99%